2013
DOI: 10.11604/pamj.2013.15.44.2006
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the usefulness of external support to immunization coverage in Chad: an analysis of the GAVI-Alliance cash-based support

Abstract: IntroductionChad is one of the countries supported by the GAVI-Alliance that remains with unsatisfactory vaccination coverage. This paper tries to understand the main barriers to better coverage.MethodsThese barriers were categorised as up or downstream against the health system building blocks as proposed by WHO and compared with barriers and activities identified by the country in its health system's strengthening grant proposal as approved by the GAVI Alliance in 2007. Data were collected using a modified D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…The lack of focus on human resources and other “upstream” efforts has been a focus of past Gavi HSS critiques [ 32 , 33 ], and this was clearly an issue in Chad, which spent none of the over $200 million intended for human resources. Human resource challenges exemplify the circular logic of HSS grants that implicitly expect countries to possess the very capacities they are aiming to improve [ 34 ]. Human resources and managerial capacity have long been recognized as key barriers program implementation for Gavi, Cameroon and Chad [ 18 , 35 ] so it is unsurprising that managerial and health worker training were integral components of these countries’ HSS proposals.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of focus on human resources and other “upstream” efforts has been a focus of past Gavi HSS critiques [ 32 , 33 ], and this was clearly an issue in Chad, which spent none of the over $200 million intended for human resources. Human resource challenges exemplify the circular logic of HSS grants that implicitly expect countries to possess the very capacities they are aiming to improve [ 34 ]. Human resources and managerial capacity have long been recognized as key barriers program implementation for Gavi, Cameroon and Chad [ 18 , 35 ] so it is unsurprising that managerial and health worker training were integral components of these countries’ HSS proposals.…”
Section: Discussionmentioning
confidence: 99%
“…The limited findings suggest that GHI support for collecting timely health information has been valuable in some conflict-affected countries, where health information tends to be very limited [ 50 , 51 ]. For example, in Somalia, the Global Fund helped establish and maintain the national Health Management Information System that collects monthly data from hospitals in the three zones of the country.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that Global Fund grants in fragile states did not perform as well as in stable resource-poor countries [ 61 ], with weak governance, corruption and poor leadership consistently identified as constraints in conflict-affected countries [ 36 , 51 , 61 ]. We could identify no studies providing evidence on specific ways in which GHIs seek to strengthen governance and leadership within the health system.…”
Section: Resultsmentioning
confidence: 99%
“…The higher HBsAg prevalence may be due to the fact that students were largely part of a relatively young but not young enough population. Indeed, with an average age of 24±3 years, our subjects most likely did not benefit from vaccination against HBV in childhood as part of the Expanded Program on Immunization introduced in 2008 [ 19 ]. Outside of that program, the relatively onerous price of the HBV vaccine is not covered by the current Chadian healthcare system, which acts as a barrier to large coverage in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2000s and with the goal of preventing transmission of HBV during childhood, several sub-Saharan countries began adding the HBV vaccine to their Expanded Programs on Immunization. This includes Chad, where the vaccine was added to its national plan in 2008 [ 19 ]. Despite this policy, the prevalence of HBV infection continues to increase, especially in the population over 15 years of age (incidence of 26.46% versus a national incidence of 13.62%) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%